Caribbean Report 21-04-1995 - Rowe, Yvette (anchor); Ninvalle, Pete (correspondent); Hinkson, Chester (interviewee); Benjamin, John (interviewee); Richards, Ken (correspondent); Irish, George (interviewee); Carrington, Edwin (interviewee); Ransome, Debbie (correspondent); Thompson, Pat (interviewee); Fraser, Tony (correspondent); Stewart, Taimoon (interviewee); Rohlehr, Gordon (interviewee); et al. (The British Broadcasting Corporation, 1995)
In Saint Lucia there continues to be concerns over the missing UN funds but there have been no calls for government resignations. The tenth meeting of the Executive Committee of the Caribbean Association of Indigenous Banks (CAIB) opened in St. Lucia. Caribbean students are having a hard time coping in the American education system according to the Caribbean Research Center. Head of the Center, Dr. George Irish comments on some of the problems facing Caribbean students. CARICOM Secretary-General, Dr. Edwin Carrington has called for more private sector involvement in regional decision making. Caribbean Association of Industry and Commerce (CAIC), Chief Executive Pat Thompson states that the onus was on CARICOM governments to invite the private sector to key conferences. A German importer of bananas from Latin America has lodged a complaint with the German Constitutional Court against the EU's import rules. Twenty- five years after the black power movement, Trinidad and Tobago reflects on the quest for black power and what has been achieved in the intervening years. Dr. Gordon Rohlehr and Selwyn Ryan comment on the need for black consciousness.
1. Headlines with Yvette Rowe (00:00-00:24)
2. In Saint Lucia concerns continue over missing UN funds but there are no calls for government resignations (00:25-01:09)
3. Report on the tenth meeting of the Executive Committee of the Caribbean Association of Indigenous Banks (01:10-03:59)
4. Caribbean students are having a hard time coping with the American education system (04:00-06:17)
Keywords: Saint Lucia -- Politics and government; Political corruption -- Saint Lucia; Scandals -- Saint Lucia; Banks and banking -- Caribbean Area; Economic development -- Caribbean Area; Financial institutions -- Caribbean Area; Immigrants -- Education -- United States; West Indians -- Education -- United States; Academic achievement -- Caribbean Area; Public-private sector cooperation -- Caribbean Area; Decision making -- Caribbean Area; Banana trade; Competition, Unfair -- European Union countries; Germany -- Foreign economic relations; Restraint of trade -- European Union countries; Black power -- Trinidad and Tobago; Blacks -- Trinidad and Tobago; Trinidad and Tobago -- Race relations; Caribbean Community; Caribbean Association of Industry and Commerce